The Infant Behavior Questionnaire – Revised: psychometric properties at 2 weeks, 3, 6 and 12 months of life - Dias, Cláudia Alexandra Castro (2021)
Background: Temperament characteristics are key elements for infants’ development. The Infant Behavior Questionnaire – Revised (IBQ-R) is one of the most used measures to assess temperament in infants aged between 3 and 12 months. Its reliability and factor structure have not yet been examined in infants younger than 3 months. Aims: To analyze the reliability of the IBQ-R at 2 weeks and the IBQ-R factor structure from 2 weeks to 12 months of life. Method: A longitudinal repeated measures design was used. Three hundred mothers completed the IBQ-R when their infants were 2 weeks, and 3, 6 and 12 months. Results: At 2 weeks the proportion of “non-applicable” responses was higher in duration of orienting, high intensity pleasure, approach and smiling and laughter scales. The Cronbach’s alpha for the IBQ-R dimensions ranged between 0.62 and 0.63 and the McDonald’s omega ranged between 0.67 and 0.80, all dimensions exhibited a mean-scale correlation above 0.15, and more than half of the scales revealed a scale-dimension correlation higher than 0.30. The same factor structure was found at 2 weeks, and at 3, 6, and 12 months: surgency/extraversion, p < 0.001, negative affectivity, p < 0.001, and orienting regulation, p = 0.007. Conclusions: The IBQ-R may be applied in the first weeks of life and its factor structure remains stable when applied across different ages throughout infancy.